Competitive Analysis in Satellite Ground Segment Industry Case Study of PT PC - Anggha Dipa Pratama; Lorio Purnomo; Glory Aguzman (Komunitas Dosen Indonesia, 2024)
The industry of providing devices and system integrators satellite ground segment is currently starting to erode with more efficient replacement telecommunications technologies such as fiber optic, wireless, and so on. In addition, satellite companies have begun to enter systems integrators business as one stop solution for customers. So, it is necessary for the provider of satellite ground segment devices and systems to re-analyze and to adjust their business strategy, to be more competitive, grow, avoid stagnation and losses. This paper used description methodology with case studies. PT PC in this case study is one of the ground segment satellite devices and system integrator company in Indonesia. This paper analyzes and provides points of advice to be done related to the results of the company's conclusions on situations and conditions using Michael Porter's 5 competitive forces and Business Model Canvas. As a result of the analysis, PT PC should strengthen the company with its uniqueness and upgrade the expertise, get more buyers and suppliers, and do diversification products and services to offset the substitutes. This paper has limitations which could be further interesting topics for the next paper.